Combination of graphene oxide and platelet-rich plasma improves tendon–bone healing in a rabbit model of supraspinatus tendon reconstruction. Issue 6 (4th August 2021) - Bao, Dingsu; Sun, Jiacheng; Gong, Min; Shi, Jie; Qin, Bo; Deng, Kai; Liu, Gang; Zeng, Shengqiang; Xiang, Zhou; Fu, Shijie
Abstract: The treatment of rotator cuff tear is one of the major challenges for orthopedic surgeons. The key to treatment is the reconstruction of the tendon–bone interface (TBI). Autologous platelet-rich plasma (PRP) is used as a therapeutic agent to accelerate the healing of tendons, as it contains a variety of growth factors and is easy to prepare. Graphene oxide (GO) is known to improve the physical properties of biomaterials and promote tissue repair. In this study, PRP gels containing various concentrations of GO were prepared to promote TBI healing and supraspinatus tendon reconstruction in a rabbit model. The incorporation of GO improved the ultrastructure and mechanical properties of the PRP gels. The gels containing 0.5 mg/ml GO (0.5 GO/PRP) continuously released transforming growth factor-β1 (TGF-β1) and platelet-derived growth factor (PDGF)-AB, and the released TGF-β1 and PDGF-AB were still at high concentrations, ∼1063.451 pg/ml and ∼814.217 pg/ml, respectively, on the 14th day. In vitro assays showed that the 0.5 GO/PRP gels had good biocompatibility and promoted bone marrow mesenchymal stem cells proliferation and osteogenic and chondrogenic differentiation. After 12 weeks of implantation, the magnetic resonance imaging, micro-computed tomography and histological results indicated that the newly regenerated tendons in the 0.5 GO/PRP group had a similar structure to natural tendons. Moreover, the biomechanical results showed that the newly formed tendons in the 0.5 GO/PRP group had better biomechanical properties compared to those in the other groups, and had more stable TBI tissue. Therefore, the combination of PRP and GO has the potential to be a powerful advancement in the treatment of rotator cuff injuries.